A prospective comparative study of mini-open versus arthroscopic repair of supraspinatus tear - Chebbi, Pavan Kumar; Rana, Manik; M., Muthu Kishore (International Journal of Research in Orthopaedics, 2020)
Background: Supraspinatus tear is very common and more frequent among older individuals. Before the arthroscopy came into high demand, the open repair of supraspinatus tear was the preferred method of surgery. Recently, the mini-open technique of repair has also gained popularity because of certain factors like better repair strength, requires less expertise and facilitates early active mobilization. Still, the gold standard modality of repair is yet to be determined as both modalities are associated with good clinical outcomes and both have their pros and cons. We decided to compare functional and clinical outcomes of arthroscopic and mini-open repair. Methods: This was a randomised study with 32 patients in each group, aged between 18 and 60 years and all patients were cases of traumatic tear of Supraspinatus tendon. From January 2016 to March 2018, alternate patients were selected for mini-open and arthroscopic repair who fulfilled our criteria. Results: Follow up was done after 12 months postoperatively and the results were evaluated using University of California Los Angeles (UCLA) shoulder score. None left the study. In arthroscopic group, out of 32 patients, 28 got excellent or good result whereas in mini open out of 32 patients 27 achieved excellent or good outcome. Conclusions: Arthroscopic method provides better visualization of shoulder anatomy whereas Mini-open method has better repair strength and is affordable. The necessity of an arthroscopy set up might not be required for supraspinatus repair as both the modalities show similar functional and clinical outcomes, reducing the economic burden on the patients.